The dynamics of financial making based on gender and tribe by SMEs - Suyati, Sri (Opción, 2019)
The purpose of this research is conducted by the financial decision making of women in small and medium micro enterprises wingko babad in Semarang, and the gender-based via a qualitative approach to explore in depth. The research results show that the women as the manager cannot make decisions by reason of blame, did not even have the authority to decide, for decision making by the family. It can happen because of history and culture in the family. Conclusions on this situation of female carries harmonization in the business of giving credence to financial decision making.